PROTECTION AND PRESERVATION SEA ENVIRONMENT IN INTERNATIONAL LAW PERSPECTIVE - Djatmiko, Agoes; Pudyastiwi, Elisabeth (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2020)
Protection of the marine environment within the framework of international law is actually an accumulation of The Principle of National Sovereignity and The Freedom of High Sea. The International Maritime Organization (IMO) states that